2021
DOI: 10.1155/2021/9999863
|View full text |Cite|
|
Sign up to set email alerts
|

Nursing Research of Optic Canal Decompression Operation under Nasal Endoscopic Medical Treatment Based on Intelligent Internet of Things for Traumatic Vision Disorders

Abstract: Traumatic vision is an important factor that causes people to have a vision. In our country, the vast majority of vision is caused by trauma. To understand the role of optic nerve decompression in the treatment of traumatic visual disturbances based on the pathological states of traumatic visual disturbances and intelligent Internet of tumors medical nasal endoscopy optic nerve decompression. This article collects relevant information by investigating patients, investigating relevant literature, interviewing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The brilliant clinical framework built in this study utilizes a versatile terminal to gather the physiological data of the human body, and the gathered physiological data will be communicated to the shrewd clinical stockpiling and handling terminal through the remote organization in the briefest time by the terminal framework [ 13 , 14 ]. The capacity and handling framework module will understand the constant stockpiling of the client's physiological data input from every terminal.…”
Section: Smart Healthcare and Related Methodsmentioning
confidence: 99%
“…The brilliant clinical framework built in this study utilizes a versatile terminal to gather the physiological data of the human body, and the gathered physiological data will be communicated to the shrewd clinical stockpiling and handling terminal through the remote organization in the briefest time by the terminal framework [ 13 , 14 ]. The capacity and handling framework module will understand the constant stockpiling of the client's physiological data input from every terminal.…”
Section: Smart Healthcare and Related Methodsmentioning
confidence: 99%
“…Visual analysis is a new analysis method; it is used in the field of mental health; under the influence of visual analysis, many characteristics of mental health are beginning to show up, but research on this aspect is still in its infancy. Simultaneously showing the mental state and personality characteristics through visual analysis, there are relatively few research studies on mining potential information; visualization converts data into visual elements such as graphics, symbols, colors, and textures that are easily perceivable by the human eye, and it can effectively enhance the efficiency of feature recognition and efficiently transmit valuable information [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%